Investigation on the effect of direct welding heat for on-stream repair of stainless steel piping - Ariffin, Eddy Azrai; Munir, Fudhail Abdul; Rahman, Abdul Razak Abdul; Yob, Mohd Shukri (2023)
Hydrocarbon leaks from piping in petroleum refinery or petrochemical plant is a process safety concern that can affect safety of personnel and plant efficiency. Piping leaks can be caused by many factors. One of the most common causes is corrosion that results in wall thinning before leaking. In some extent, consistent vibration of the pipe will also lead to crack formation and subsequently leakage. Thinning pipes may be repaired without shutting down the plant depending on the severity of the wall loss. There are ways to perform online repair on process piping as specified by American Petroleum Institute (API) 570 Piping Inspection Code. For example, it can be repaired by performing on-stream welding either by using full encirclement welded split sleeve enclosure or patch, or by weld build up repair. The former is categorized as temporary repair. In this paper, a study was performed to examine two methods of on-stream welding repair namely build up welding and patch welding, and to investigate the effect on temperature and integrity of the piping. The specimen used was a 10-inch Schedule 10 ASTM A/SA312 TP304L Austenitic Stainless Steel pipe. A mock test rig that represents the actual site condition was prepared. Burn through marks and maximum inner surface temperature of the pipe were examined. The results suggest that build up welding method is too risky to be performed as on-stream repair as the inner surface temperature is too high which will cause the flammable product inside the pipe to ignite and lead to fire.